The Fifteenth-century inquisitions 'post mortem' : a companion - Hicks, Michael, 1948- (The Boydell Press, 2012)
The Inquisitions Post Mortem (IPMs) at the National Archives have been described as the single most important source for the study of landed society in later medieval England. Inquisitions were local enquiries into the lands held by people of some status, in order to discover whatever income and rights were due to the crown on their death, and provide details both of the lands themselves and whoever held them. This book explores in detail for the first time the potential of IPMs as sources for economic, social and political history over the long fifteenth century, the period covered by this Companion. It looks at how they were made, how they were used, and their "accuracy", and develops our understanding of a source that is too often taken for granted; it answers questions such as what they sought to do, how they were compiled, and how reliable they are, while also exploring how they can best be used for economic, demographic, place-name, estate and other kinds of study.
Keywords: Great Britain -- History -- Lancaster and York, 1399-1485 -- Sources.; Inquisitiones post mortem -- England -- History -- 15th century.; Grande-Bretagne -- Histoire -- 1399-1485 (Lancastre et York) -- Sources.; HISTORY -- Medieval.; Inquisitiones post mortem; England; Great Britain; 1399-1499; IPMs.; Inquisitions Post Mortem.; demographic study.; economic history.; estate study.; landed society.; medieval England.; political history.; social history.; Electronic books.; History; Sources